Analisis Kinerja Guru IPS Pasca Sertifikasi di SMP Negeri Kota Tarakan - Sukono . (Jurnal Kebijakan dan Pengembangan Pendidikan, 2015)
Analisis Kinerja Guru IPS Pasca Sertifikasidi SMP Negeri Kota TarakanSukonoPengawas Sekolah Dinas Pendidikan Kota TarakanEmail: Sukono nono@yahoo.comAbstract:The approach in this research was quantitative and qualitative. Quantitative approach was used to acquire the data of the assessment of teacher’s performance. Meanwhile, qualitative was used to acquire the data of teachers’ interview result related to teachers’ main duty, the supporting factors of teacher’s performance and its inhibiting factors. The results showed that social science teacher’s performance of Junior High School in Tarakan in the dimension of learning implementation overall had met the performance with the average ‘fair’. The supporting factors of teacher’s performance reached the average ‘good’ category as follows: 1) sufficient facility and infrastructure; 2) teacher’s welfare was concerned; 3) principal’s support was very good; 4) the enhancement of teacher competency was concerned; 5) the supporting condition of school environment; 6) reward for teachers who achieve excellent. Inhibiting factors of teachers’ performance, namely: 1) school’s facility and infrastructure had not been sufficient; 2) less support from principal; 3) learning media were still lacking, and 4) less supporting school environment.Keywords: teachers’ performance, main duty of teachers, teacher certification.Abstrak:Pendekatan dalam penelitian ini adalah kuantitatif dan kualitatif. Pendekatan kuantitatif digunakan untuk memperoleh data penilaian kinerja guru, sedangkan kualitatif digunakan memperoleh data hasil wawancara guru berkaitan tugas utama guru, faktor-faktor pendukung kinerja guru dan faktor-faktor penghambat kinerja guru. Hasil penelitian menunjukkan bahwa kinerja guru IPS jenjang SMP di kota Tarakan pada dimensi pelaksanaan pembelajaran secara keseluruhan telah memenuhi kinerja dengan rata-rata cukup. Faktor pendukung kinerja guru mencapai rata-rata kategori baik antara lain: 1) sarana prasarana yang memadai; 2) kesejahteraan guru di diperhatikan; 3) dukungan Kepala Sekolah sangat baik; 4) peningkatan kompetensi guru diperhatikan; 5) kondisi lingkungan sekolah yang mendukung; 6) reward bagi guru yang berprestasi. Faktor-faktor penghambat kinerja guru, yaitu: 1) sarana prasarana sekolah belum memadai; 2) dukungan dari Kepala Sekolah kurang: 3) media pembelajaran masih kurang, dan 4) lingkungan sekolah yang kurang mendukungKata kunci: kinerja guru, tugas utama guru, sertifikasi guru.